CD44: can a cancer-initiating cell profit from an abundantly expressed molecule? - Zöller, Margot (Nature reviews. Cancer, 2011)
CD44, the major hyaluronan (HA) receptor, makes abundant use of alternative splicing and can be located in glycolipid-enriched microdomains (GEMs). The extracellular and the cytoplasmic domains can associate with a large array of molecules.Cancer-initiating cells (CICs; also known as cancer stem cells) constitute a minor population of cells within a tumour, but are frequently essential for tumour maintenance and progression. CICs can be enriched by so-called CIC markers, the most common of which is CD44.CD44 can contribute to the activation of stem cell regulatory genes and can be a target of these genes, but there is, at present, no compelling evidence that CD44 has a central role in self-renewal and maintenance of pluripotency.CD44 binding to HA has an important role in haematopoietic stem cells (HSCs) and leukaemia-initiating cells (LICs) and probably CIC homing and adhesion. HA binding-induced changes in CD44 membrane localization and conformation trigger the association and activation of multiple signal transduction molecules and of proteases, which supports migration.CD44 accounts for the homing and settling of adult stem cells (ASCs), as well as metastasizing tumour cells and CICs in the niche, is actively involved in niche assembly through its effect on HA secretion and degradation, mainly owing to its activity as a catcher of chemokines, growth factors and matrix-degrading enzymes.The HA-CD44 and HA-CD44v interactions have a central role in receptor tyrosine kinase (RTK)-induced activation of anti-apoptotic pathways and actively promote tumour cell and possibly CIC survival through their associations with multidrug resistance genes. Importantly, activation of signalling pathways initiated by the tumour matrix could be inhibited by HA degradation, by competition with small HA fragments, by CD44 blockade or by CD44 knockdown, whereas a blockade of an individual RTK did not recapitulate all of the effects observed on inhibition of CD44-HA binding.
Gesehen am 23.01.2023